Pengaruh External Pressure, Financial Target, And Financial Stability Pada Kecurangan Laporan Keuangan - Indah Septiani; Satiman (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to determine the effect of external pressure, financial targets, and financial stability on financial statement fraud (an empirical study of healthcare sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period) both simultaneously and partially. This type of research is quantitative. The population in this study was 37 companies, the sample in this study was obtained using a purposive sampling technique, resulting in 8 samples for the 2019-2023 period. The data used in this study were obtained from financial statements. The tests used in this study were descriptive statistical tests, panel data regression estimation model selection, classical assumption tests, and hypothesis tests. To answer the research problem, the data were analyzed using Eviews 12. The results of this study are based on simultaneous tests of external pressure, financial targets, and financial stability that influence financial statement fraud, while partial tests of external pressure and financial targets do not influence financial statement fraud, but financial stability does influence financial statement fraud.